PM.54 Successful Treatment of Two Cases of Severe Aortic Stenosis in Pregnancy. (26th April 2013) - Cox, S; Stephen, G; Vause, S; Clarke, B
Abstract : Introduction: Severe aortic stenosis can result in collapse and sudden death. Cardiac morbidity during pregnancy is related to the severity of the stenosis and symptoms. Patient A: Patient A was 41 years old with known aortic stenosis and a dilated aortic root (5 cm). At 15 weeks gestation she developed dyspneoa and chest pain. An echocardiogram was performed, which showed an aortic valve gradient of 82 mmHg with a dilated aortic root. She was transferred to a tertiary unit and balloon valvuloplasty was performed, resulting in improvement of the aortic valve gradient from 82 mmHg to 50 mmHg and in symptoms. The pregnancy progressed well and she was delivered by Caesarean Section at 38 + 3 because of the dilated aortic root. Patient B: Patient B was 25 years old with a known bicuspid aortic valve and previous treatment to coarctation of the aorta. An echocardiogram at 16 weeks gestation demonstrated an aortic valve gradient of 120 mmHg. She was admitted urgently. A balloon valvuloplasty was attempted but was unsuccessful. She was counselled regarding treatment options, which included doing nothing and risking sudden death, valve replacement or termination of pregnancy. The patient opted for a valve replacement with a prosthetic valve. She had labour induced and a vaginal delivery at 37 weeks. Conclusion: Both women had successful treatment of aortic stenosis in pregnancy, reducing their risk of cardiac morbidity and maternal mortality. Close multidisciplinary working between specialist obstetric and cardiac teams is necessary to provide the most appropriate management.